Criminal Liability of COD Couriers As Narcotics Intermediaries: an Analysis of Article 114 of The Narcotics Law And the New Criminal Code - Preden Ginting; Ujuh Juhana (International Journal of Law, Crime and Justice, 2026)
The proliferation of digital commerce has enabled a new narcotics distribution mode through Cash on Delivery (COD) systems that exploit delivery couriers as intermediaries, systematically obscuring criminal trails and placing intellectual perpetrators beyond immediate risk of arrest. This study analyzes the regulation and application of criminal liability of COD couriers as narcotics intermediaries under Article 114(1) of Law No. 35 of 2009 on Narcotics, reviewed against the New Criminal Code (Law No. 1 of 2023), while critically examining the practice of proving the intent element in Bandung City. A normative-empirical legal method was employed, integrating statutory, conceptual, case-based, and comparative approaches. Empirical data were obtained from the Narcotics Criminal Investigation Unit of Polrestabes Bandung, which handled 92 cases involving 117 suspects across three monitoring periods in 2024. The research reveals that the phrase "acting as an intermediary" in Article 114(1) inherently contains an active will element requiring positive proof of intent. The New Criminal Code's Article 35 codifies the principle geen straf zonder schuld as binding positive law, while Articles 20–22 mandate proportional role differentiation among perpetrators, co-perpetrators, and accessories. In practice, however, investigators apply a presumption of knowledge derived from physical possession and uniformly categorize couriers as full perpetrators without typology assessment. This systemic gap produces over-criminalization that potentially violates suspects' constitutional rights under Article 28D(1) of the 1945 Constitution. The study recommends immediate standardization of mens rea evidentiary procedures, mandatory courier typology identification, and harmonization of the Narcotics Law with the New Criminal Code.